Mechanism of depolarization of rat cortical synaptosomes at submicromolar external Ca2+ activity. The use of Ca2+ buffers to control the synaptosomal membrane potential. - Schmalzing, G (1985)
Rat cortical synaptosomes responded to a reduction of external Ca2+ from pCa 3.5 to pCa 4.8 in the absence of MgCl2 with a slight decrease of internal K+ and an increase of Na+. The effects were prevented by tetrodotoxin or millimolar concentrations of MgCl2. Further lowering of external pCa to 7.7 with N-hydroxyethylethylenediaminetriacetate evoked a rapid fall of internal K+, which was specifically blocked by Ruthenium Red; tetrodotoxin and nifedipine were ineffective. A linear relationship was established between K+ and methyltriphenylphosphonium cation distribution ratios by varying external pCa between 4.8 and 7.7, indicating that K+ efflux resulted from a depolarization of the plasma membrane. An increase of Na+ permeability was suggested by the synaptosomes' gain of Na+ and the disappearance of the depolarization in an Na+-free sucrose medium. According to the constant field equation, the permeability ratio PNa/PK increased from 0.029 at pCa4.8 to 0.090 at pCa 7.7 with plasma membrane potentials of -74mV and -47mV, respectively. Since the plasma membrane responded to variation of external Ca2+ activities in the micromolar range with a graded and sustained depolarization, the use of Ca2+ buffers to control membrane potentials is suggested.